A comprehensive quality control and cost comparison study of branded and generic angiotensin receptor blockers - Arvind Kumar Sharma; Shruti Rastogi; Faraat Ali; Anuj Prakash Yadav; Ramesh K. Goyal (Elsevier, 2024)
This study was designed to assess both the quality and cost aspects of various branded and generic formulations of angiotensin receptor blockers, specifically Irbesartan, Losartan Potassium, Olmesartan Medoxomil, Telmisartan, and Valsartan. The collected samples underwent distinct quality evaluations using the methods outlined in different global Pharmacopoeias (British Pharmacopoeia/European Pharmacopoeia, Indian Pharmacopoeia and United States Pharmacopoeia). These drugs were characterized using Fourier-Transform Infrared Spectroscopy and Nuclear Magnetic Resonance techniques, while their quality and concentration were analysed using High Performance Liquid Chromatography. The release profile of the drugs was examined through dissolution testing. Additionally, a cost comparison analysis was carried out by determining the prevailing market prices of the drugs. The evaluated branded and generic angiotensin receptor blockers were found to meet the established standards for impurities, active drug content, and dissolution as set by these Pharmacopoeias, indicating their optimal quality. Notably, the generic drugs exhibited significantly lower costs compared to their branded counterparts. This study confirms that the quality of generic angiotensin receptor blockers is equivalent to that of their branded counterparts. Consequently, these findings support the practicality of utilizing generic drugs as a more economically sustainable and cost-effective approach to managing diseases, especially those of chronic nature.